Study of the genes alliinase and chitinase in materials of costarican garlic (Allium sativum L) - Barboza-Rojas, Karina (2013)
Garlic production in Costa Rica has been affected by the quality and quantity of the harvested seeds. Bulb production has also been deteriorated by diseases. However, this crop is preferred for its flavor, considered superior to the one imported from China. Pungency of garlic is partially due to the action of the alliinase enzyme. Furthermore, the resistance to certain pathogenic fungi is influenced by the chitinase enzyme activity. The encoding genes for both enzymes were analyzed in this study, by using in vitro plantlets obtained from local materials from Llano Grande, Santa Ana, Miramar and San Ramon zones and garlic imported from China. By using these genes, DNA sequences were compared and studied in order to find differences that allow the characterization of various materials. The results showed the presence of different alliinase gene copies. The chitinase gene presented a highly conserved sequence in all materials tested. Two highly conserved introns were found in the Costa Rican germplasm and the Asian reference material. It was concluded that Costa Rican garlic is very similar to the Asian. Also, the first report of the existence of introns in the chitinase of garlic is presented here.